Neural correlates of posttraumatic anhedonia symptoms: Decreased functional connectivity between ventral pallidum and default mode network regions. (August 2021) - Li, Gen; Cao, Chengqi; Fang, Ruojiao; Liu, Ping; Luo, Shu; Liberzon, Israel; Wang, Li
Abstract: Anhedonia is common in individuals with traumatic experience. Anhedonia symptoms play an important role in posttraumatic psychopathology, and are related to various adverse outcomes. The current study is a preliminary neuroimaging study of the neural correlates of posttraumatic anhedonia symptoms. Resting-state fMRI data were acquired from 88 Chinese earthquake survivors. Whole brain analyses and exploratory ROI-to-ROI analyses were performed to examine the relationship between posttraumatic anhedonia symptoms and resting-state functional connectivity (rsFC) of reward-related subcortical nucleus including nucleus accumbens and ventral pallidum. The rsFC between left ventral pallidum and areas of bilateral posterior cingulate cortex (PCC) and precuneus cortex were found lower in the high posttraumatic anhedonia group, after controlling for sex, age and other posttraumatic stress symptoms. The rsFC between left ventral pallidum and PCC and the rsFC between left ventral pallidum and lateral parietal cortex were significantly lower in the high anhedonia group. Our findings suggest that decreased functional connectivity between the ventral pallidum and the brain default mode network (DMN) regions could be the neural correlates of posttraumatic anhedonia symptoms.